Investigation of regional conditions and sustainability indicators for sustainable product development of building materials. (20th September 2018) - Kono, Jun; Ostermeyer, York; Wallbaum, Holger
Abstract: With the increasing importance of the sustainable product development of the building materials for the sustainable building and its industries, this study structured the existing sustainability assessment methods based on a common information structure, which was classified by its categories, aspects, and indicators. Sustainability indicator lists were structured into 25 categories, 88 aspects which 25% of those were product or product and regional related ones. Most of the sorted indicators related to products were difficult to be applied at the early phase of product development due to the lack of required level of information. Meanwhile, the indicators could be a supportive tool for the later phase of product development, for the production planning step as an example. Since the regional conditions showed the link between the sustainability performance during the building's operational phase, the conditions may serve as a proxy information to guide during the earlier product development phase. Highlights: 500+ Sustainability indicator lists were sorted in 25 categories, 88 aspects. Existing sustainability indicators can support the decision making of the later phase of product development, such as the production planning step. Regional conditions may serve as a proxy information to support the early phase of the sustainable product development.